Wykorzystanie distance learning do podniesienia jakości kształcenia w dziedzinie rachunkowości - Lew, Grzegorz (The Use of Distance Learning for Improving the Quality of Education in the Area of Accountancy, 2005)
The increasing access to Internet enables introducing others than traditional methods of teaching. The paper presents the possibilities of distance learning as the up-to-date form of teaching accountancy. In a short way the chances and dangers of introducing distance learning at Polish universities have been described, taking into account teaching accountancy. The article concludes that distance learning cannot replace the traditional method of teaching but it is a great supplement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 102-108